ANALISIS TINGKAT DEPRESI PADA SISWA SMK JAKARTA RAYA 2 - Marchelina, Leticia; Pebriyanti, Cinta; Safitri, Erlina Dian; Marisa, Cindy (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2025)
Awareness of the importance of mental health continues to grow globally, including in Indonesia. With increasing social, economic pressures, and technological advancements, mental disorders such as depression have become critical issues that significantly impact quality of life, academic performance, and social functioning, particularly among adolescents. According to WHO data, the global prevalence of depression is on the rise, with the majority of cases occurring in developing countries, including Indonesia. Adolescence, marked by emotional and psychological changes, increases vulnerability to depression, especially when combined with academic pressure, experiences of violence, and lack of emotional support. Teenagers with depression often exhibit symptoms such as prolonged sadness, social withdrawal, disturbed eating and sleeping patterns, and self-harming thoughts. Considering the high level of risk, this study aims to analyze the prevalence and contributing factors of depression among vocational high school (SMK) students. The findings are expected to serve as a foundation for developing more effective prevention and intervention strategies, as well as supporting the creation of mentally healthy learning environments. Keywords: Teenager, Depression.